Voices in Machado de Assis's short story about a fire in Montevideo - Marchezan, Luiz Gonzaga [UNESP] (My University, 2015)
In his dialogical reflection on utterance, Voloshinov emphasizes that its implied component is the one that is common to a social group and does not need thus to be explicit. In that manner, the author observes that when adding, juxtaposing memory situations in reported time and space, it is possible for the enunciator to coordinate perceptions concerning existence in fiction and to relate them to intonations that increasingly narrow the interlocution between things lived and utterances. In view of that, we analyze the short story Um incêndio [A Fire] by Machado de Assis based on a dialogical perspective. This short story was motivated by the news of a fire that had occurred in a port area of Montevideo. The news was told by the engineer Abel Ferreira de Matos, who, in turn, had heard it from the boy Manuel Bandeira.
Keywords: Brazilian literature; Dialogism; Intonation; Short story